Acute liver graft failure due to emergence of lamivudine resistant hepatitis B virus: rapid resolution during treatment with adefovir - Mutimer, D (2001)
BACKGROUND—Strategies for prevention of liver graft reinfection by hepatitis B virus (HBV) have been developed during recent years. Initially, passive immunoprophylaxis with high titre HBV immunoglobulin (HBIg), followed by lamivudine prophylaxis, and then the combination of lamivudine and HBIg have been employed. However, suboptimal use of the combination may be associated with failure of prophylaxis reflected by the emergence of HBV species with genetic changes that confer resistance to lamivudine and HBIg. Reinfection of the graft by HBV can be associated with rapid development of liver failure. CASE REPORT—A 43 year old HBV infected man received lamivudine before transplantation, and lamivudine and HBIg after transplantation. Despite prophylaxis, graft reinfection and severe hepatitis were observed. The observed serological evolution and genetic sequencing of the emergent HBV species suggested selection of lamivudine resistant and surface antigen escape mutants consecutively. Adefovir treatment began after the devlopment of graft failure. OUTCOME—A rapid exponential decline in serum HBV titre was observed. Liver function tests normalised and signs of liver failure resolved. CONCLUSION—The use of HBIg and lamivudine permits prevention of graft reinfection by HBV for the majority of patients. Adefovir, a potent inhibitor of lamivudine resistant HBV, should be used when failure of prophylaxis is associated with graft hepatitis.   Keywords: hepatitis B virus; adefovir; liver graft; lamivudine